2005
DOI: 10.1002/bit.20562
|View full text |Cite
|
Sign up to set email alerts
|

PEG conjugation moderately protects adeno-associated viral vectors against antibody neutralization

Abstract: AAV gene therapy vectors have significant clinical promise, but serum neutralization poses a challenge that must be overcome. We have examined the potential of conjugating the AAV surface with activated polyethylene glycol chains to protect the vector from neutralizing antibodies. Two key parameters were investigated: the polymer chain size and the PEG:lysine conjugation ratio. Transduction data revealed that the vector is fully infectious until a critical PEG conjugation reaction ratio was exceeded, and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 73 publications
(93 reference statements)
1
118
0
1
Order By: Relevance
“…To overcome AAV NAb inhibition of AAV vector transduction, several approaches have been exploited in the lab. One of them is to use a polymer to cover the AAV surface and block NAb recognition (11,32,33). The second approach is to use error-prone PCR to generate a library of AAV variants and select for NAb escape mutants in the presence of NAb in vitro (31,41,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome AAV NAb inhibition of AAV vector transduction, several approaches have been exploited in the lab. One of them is to use a polymer to cover the AAV surface and block NAb recognition (11,32,33). The second approach is to use error-prone PCR to generate a library of AAV variants and select for NAb escape mutants in the presence of NAb in vitro (31,41,56).…”
Section: Discussionmentioning
confidence: 99%
“…These findings present a concern to the gene therapy community as to how we can avoid antagonistic NAb activity during systemic delivery of AAV vectors. To overcome this concern, several approaches have been exploited in our lab and by other groups, including (i) the utilization of polymers to cover the AAV capsid and block NAb recognition (11,32,33), (ii) the development of NAb escape mutants by error-prone PCR in vitro (31,41,56), (iii) the application of other types of AAV vectors (27,30,38,60,65), and (iv) the generation of chimeric types via AAV shuffling (2,36,37). In this study, we have systematically explored the possibility of using different types and AAV mutants as alternative vectors for intramuscular gene delivery in mice preimmunized against different AAV types.…”
mentioning
confidence: 99%
“…Pegilasyon işlemi sonucu elde edilen konjugatlar aşağıda belirtilen özellikleri göstermektedir(Şekil 4) [2,7,[8][9][10][11][12][13][14][15]]. …”
Section: Peg-etkin Madde Konjugatlarının Avantajlarıunclassified
“…[15][16][17][18][19] However, studies have shown that chemical conjugation reduced infection activity of Adv, associated with steric hindrance from flexible polyethylene glycol (PEG) chains, resulting in a decreased gene transduction and transgenic expression. 16,20,21 This can be partially compensated for by a targeted ligand covalently conjugated to the PEG (ligand-PEG-Adv). 22,23 Moreover, chemical conjugation showed protection of Adv in a titer-related way, but still failed in complete avoidance of the immune response or a negligible influence by NAb.…”
Section: Introductionmentioning
confidence: 99%